Negative feedback regulation of alcohol ingestion through the FGF21-PVH oxytocin-VTA dopamine system - Sho Matsui; Yuma Takahashi; Shuhei Morioka; Takaaki Ozawa; Sachiho Kanayama; Hiroki Iwama; Lan Geng; Kazuhiro Umemoto; Yasuo Oguri; Satoshi Tsuzuki; Yulong Li; Takatoshi Hikida; et al. (Proceedings of the National Academy of Sciences, 2026)
Alcohol has a notable negative impact on global health. Understanding its physiological regulation is crucial to addressing alcohol use. Here, we show that FGF21-oxytocin neurons in the paraventricular nucleus of the hypothalamus (PVH OXT )-dopamine neurons in the ventral tegmental area (VTA DA ) negatively regulate the drive to drink alcohol. Alcohol induces FGF21 signaling, which activates PVH OXT and induces oxytocin release in the VTA. The VTA DA neurons are activated hours after alcohol ingestion, which reduces the drive to drink alcohol, extends the interdrink interval, and thereby reduces alcohol consumption. The system is downregulated in a mouse model of alcohol dependence, and activating the system with FGF21-inducing sugars reduces alcohol ingestion and prevents binge drinking and alcohol dependence. Therefore, FGF21-inducing nutraceuticals can substitute for alcohol by supplementing the FGF21-PVH OXT -VTA DA negative feedback signal to attenuate alcohol-related behaviors in mice.